Analisis Penerapan Manajemen Kompensasi Adhered dan Overlapping Pada UKM XYZ (International Forum of Researchers and Lecturers, 2024)
Effective compensation management is a key factor for the success and sustainability of Small and Medium Enterprises (SMEs). This study aims to analyze the implementation of adhered and overlapping compensation management at XYZ SME in Subang Regency, West Java. Data were collected through questionnaire surveys, interviews, and documentation studies related to compensation policies and employee salary structures. Data analysis included salary mapping using the adhered and overlapping methods, and job evaluation using the Eckenrode system. The results showed that the majority of employees of XYZ receive basic salaries below the Provincial Minimum Wage (UMP) and Regency/City Minimum Wage (UMK). The implementation of adhered and overlapping compensation management is expected to improve the internal fairness of the compensation system and provide ideal salary recommendations for employees. The findings of this study provide valuable insights for similar SMEs in optimizing compensation strategies to maintain competitiveness, increase satisfaction, and boost employee productivity.